Detection of BoLA-DRB3 gene polymorphism in Gir and Kankrej cattle using PCR-RFLP - ACHARYA, C P; PIPALIA, D L; RANK, D N; JOSHI, C G; SOLANKI, J V; SHAH, R R (The Indian Journal of Animal Sciences, 2014)
BoLA-DRB3 gene polymorphism was investigated in 2 cattle breeds, Gir and Kankrej by PCR-RFLP. Genomic DNA was isolated from blood samples collected from 57 Gir and 51 Kankrej animals. A 284 bp BoLA - DRB3 exon2 segment was amplified by hemi-nesting PCR, using the locus specific primers and the PCR products were subjected to Hae III and Rsa 1 digestion. Digestion with Hae III resulted in 3 RFLP patterns a, band din 5 different combinations (aa, ab, ad, bb and bd) in Gir, and 3 RFLP patterns a, band e in 4 different combinations (aa, ab, ae and be) in KankreJ. Pattern a and b were more frequent in both the breeds. Rsa 1 restriction patterns were very complex. The fragment interpretations evealed 13 different restriction patterns with 25 combinations in Gir and 10 different combinations in Kankrej. Thus, BoLA DRB3 was highly polymorphic.